2020
DOI: 10.1177/1940161220960415
|View full text |Cite
|
Sign up to set email alerts
|

Biomedicalization and Media in Comparative Perspective: Audiences, Frames, and Actors in Norwegian, Spanish, U.K. and U.S. Health News

Abstract: This study examines health news in Norwegian, Spanish, British, and U.S. newspapers. It seeks to fill a gap in journalism studies in the examination of health news as a genre, particularly in a comparative context, and with a focus on broader social and political roles and meanings of health news, rather than effects on individual behavior. It is rooted in literatures that seek to understand health journalism in sociological terms, considering the role of health journalism in relation to institutional relation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
19
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 40 publications
(43 reference statements)
4
19
0
1
Order By: Relevance
“…Health sourcing has been analyzed from the perspective of credibility, expertise, and trustworthiness in that sources must show competence, report accurate information, and make valid assertions (McCroskey and Young 1981;Metzger and Flanagin 2015). Health communication and journalism research has shown that there is a tendency among journalists to perceive scientists and biomedical researchers as authoritative experts and neutral sources, and to seek "white coats" to give credibility to the news (Forsyth et al 2012;Hinnant, Len-R ıos, and Oh 2012;Len-R ıos et al 2009, p. 318;Hallin, Figenschou, and Thorbjørnsrud 2021).…”
Section: Sourcing Health Newsmentioning
confidence: 99%
See 4 more Smart Citations
“…Health sourcing has been analyzed from the perspective of credibility, expertise, and trustworthiness in that sources must show competence, report accurate information, and make valid assertions (McCroskey and Young 1981;Metzger and Flanagin 2015). Health communication and journalism research has shown that there is a tendency among journalists to perceive scientists and biomedical researchers as authoritative experts and neutral sources, and to seek "white coats" to give credibility to the news (Forsyth et al 2012;Hinnant, Len-R ıos, and Oh 2012;Len-R ıos et al 2009, p. 318;Hallin, Figenschou, and Thorbjørnsrud 2021).…”
Section: Sourcing Health Newsmentioning
confidence: 99%
“…The literature tends to show that overall, medical professionals and health specialists, academics, and government authorities and politicians continue to be the most important voices in news coverage by traditional media (Atkin et al 2008;De Dobbelaer et al 2018;Oh, Kwon, and Raghav Rao 2010;Stroobant, De Dobbelaer, and Raeymaeckers 2018;Wu 2006;Hallin, Brandt, andBriggs 2013 Hallin, Figenschou, andThorbjørnsrud 2021). Some studies have found that the presence of citizens as sources in health news is comparatively low (Rowe et al 2003) and is actually completely absent in the coverage of some diseases (Clarke 2006).…”
Section: Sourcing Health Newsmentioning
confidence: 99%
See 3 more Smart Citations